2007
DOI: 10.1128/jvi.02535-06
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Human Immunodeficiency Virus (HIV) Gag-Specific CD8+T-Cell Responses in Rectal Mucosa and Peripheral Blood Mononuclear Cells during Chronic HIV Type 1 Infection

Abstract: The intestinal tract is a lymphocyte-rich site that undergoes severe depletion of memory CD4؉ T cells within days of simian immunodeficiency virus or human immunodeficiency virus type 1 (HIV-1) infection. An ensuing influx of virus-specific CD8 ؉ T cells, which persist throughout the chronic phase of infection, has also been documented in the gastrointestinal tract. However, little is known of the functionality of these effector cells or their relationship to the disease course. In this study, we measured CD8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
95
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(102 citation statements)
references
References 64 publications
7
95
0
Order By: Relevance
“…The lack of comparably high levels of viral replication within other mucosal sites may thus allow for preservation of local CD4 T cells and the successful induction and maintenance of HIV-specific T-cell responses. Consistent with this explanation, HIV-specific T cells have been detected in rectal biopsies of HIV-infected humans, [12][13][14]33 and CD4 T-cell depletion in the colon may be less severe than depletion in the small intestine. 13,33 In addition, Mamu A01 + rhesus macaques attain significantly lower set point VLs after SIV infection compared to rhesus macaques that do not express the A01 allele, 34 and these monkeys manifest high frequencies of Mamu-A01-restricted SIV-specific CD8 T cells in both small and large intestines.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The lack of comparably high levels of viral replication within other mucosal sites may thus allow for preservation of local CD4 T cells and the successful induction and maintenance of HIV-specific T-cell responses. Consistent with this explanation, HIV-specific T cells have been detected in rectal biopsies of HIV-infected humans, [12][13][14]33 and CD4 T-cell depletion in the colon may be less severe than depletion in the small intestine. 13,33 In addition, Mamu A01 + rhesus macaques attain significantly lower set point VLs after SIV infection compared to rhesus macaques that do not express the A01 allele, 34 and these monkeys manifest high frequencies of Mamu-A01-restricted SIV-specific CD8 T cells in both small and large intestines.…”
Section: Discussionmentioning
confidence: 62%
“…Consistent with this explanation, HIV-specific T cells have been detected in rectal biopsies of HIV-infected humans, [12][13][14]33 and CD4 T-cell depletion in the colon may be less severe than depletion in the small intestine. 13,33 In addition, Mamu A01 + rhesus macaques attain significantly lower set point VLs after SIV infection compared to rhesus macaques that do not express the A01 allele, 34 and these monkeys manifest high frequencies of Mamu-A01-restricted SIV-specific CD8 T cells in both small and large intestines. [35][36][37] Moreover, Mamu-A01 + rhesus macaques that fail to control viral replication lack functional SIV-specific CD8 T cells in mucosal sites.…”
Section: Discussionmentioning
confidence: 62%
“…Although data on mucosal HIV-specific immunity during the acute phase of infection are scant, recent studies have investigated HIV-specific T-cell immunity in rectal biopsies of chronically HIV-infected individuals. 63,64 Initially, these studies were restricted to the physical examination of HIVspecific CD8 T cells using peptide-major histocompatibility complex tetramer technology. 63 These studies demonstrated that HIV-specific CD8 T cells were detectable in the GI tract and that the frequency of HIV-specific CD8 T cells in the GI tract was similar to that observed in peripheral blood, approximately 1% of CD8 T cells.…”
Section: Gastrointestinal Hiv-specific Immune Responsesmentioning
confidence: 99%
“…67 In addition, in a cohort of chronically HIV-infected individuals, the functional capacity of HIV-specific CD8 T cells in rectal biopsies was studied; these cells were observed to be similarly skewed toward a predominant "monofunctional" profile (mobilization of CD107a without effector cytokine production), similar to the functional capacity observed in the peripheral blood of chronically infected individuals. 64 In contrast, individuals who are able to control viral replication maintain a polyfunctional T-cell response in peripheral blood. 66 Taken together, these findings strongly suggest that a successful HIV vaccine should induce polyfunctional HIV-specific CD8 T cells within the GI tract.…”
Section: Gastrointestinal Hiv-specific Immune Responsesmentioning
confidence: 99%
“…It stands to reason that a preventive or disease attenuating vaccine should elicit CTL responses that access this compartment. It has been observed that HIV-1-specific CTL are found among gut lymphocytes in chronically-infected persons [25,26], but whether rAd5 vaccination elicits CTL in the gut remains unknown. Data comparing gut shedding of poliovirus in persons who had previously received inactivated versus live-attenuated poliovirus vaccine suggested that mucosally administered replicating vaccines may yield better mucosal immunity [27,28].…”
Section: Trafficking Of Ctl Where They Are Neededmentioning
confidence: 99%